PENGARUH KOMITMEN AFEKTIF, KOMITMEN KONTINUAN DAN KOMITMEN NORMATIF TERHADAP KINERJA PEGAWAI DINAS KEPENDUDUKAN DAN CATATAN SIPIL KABUPATEN PAMEKASAN - jurnalmap map; DIDIK DARMADI; Woro Utari; Subijanto ÔÇì (MAP (Jurnal Manajemen dan Administrasi Publik), 2020)
ABSTRACT This research was conducted in the civil registry of Kabupaten Pamekasan. with a total sample of 44 people. The purpose of this study is 1). To know and describe how well affective commitment, continuance commitment, and normative commitment in the Department of Population and Civil Registry, 2). To know and examine the simultaneous influence of organizational commitment factors on the performance, 3). To find out and test the partial influence on the performance. The results show that normative commitment as an attitude that describes the individual's orientation towards the organization. Affective commitment relates to the emotional, identification, and involvement of employees within an organization. A continuous component means a component based on the employee's perception of the disadvantage he will face if leaving the organization. Simultaneously, affective commitment, continuous commitment and normative commitment have a very significant effect on the performance. Partially, affective commitment have a significant influence on the performance. Continuous commitment variables have a dominant influence in influencing the performance of employees of the Department of Population and Civil Registry of Kabupaten Pamekasan. Keywords: Affective Commitment (X1), Continuous Commitment (X2), Normative Commitment (X3) and Employee Performance (Y).